PRAGMATIC ANALYSIS OF SPEECH ACTS IN PRESIDENT PRABOWO SUBIANTO’S REMARKS AT THE HIGH-LEVEL INTERNATIONAL CONFERENCE - Lestari, Triana (Jurnal Warta Dharmawangsa, 2025)
This study identifies the types and purposes of speech acts contained in President Prabowo Subianto's speech at the High-Level International Conference for the Peaceful Settlement of Palestine and the Implementation of the Two-State Solution (New York, 2025). This study uses Searle's (1979) classification of speech acts: representatives, directives, commissives, expressives, and declaratives. This research was conducted qualitatively and focused on how language functions as a tool for political action and persuasion. Using a descriptive pragmatic approach, the analysis shows that all five types of speech acts appeared in the speech. Representative speech acts affirm Indonesia's humanitarian position, directive speech acts call for international cooperation, commissive speech acts express commitment to the future, expressive speech acts demonstrate empathy and respect, and declarative speech acts demonstrate diplomatic intent. The study concludes that President Prabowo's speech reflects Indonesia's moral, diplomatic, and humanitarian leadership through the strategic and persuasive use of language in the context of international diplomacy.